Is monitoring of plasma 5-fluorouracil levels in metastatic / advanced colorectal cancer clinically effective? A systematic review. Issue 1 (December 2016) - Freeman, Karoline; Saunders, Mark; Uthman, Olalekan; Taylor-Phillips, Sian; Connock, Martin; Court, Rachel; Gurung, Tara; Sutcliffe, Paul; Clarke, Aileen
Abstract Background Pharmacokinetic guided dosing of 5-fluorouracil chemotherapies to bring plasma 5-fluorouracil into a desired therapeutic range may lead to fewer side effects and better patient outcomes. High performance liquid chromatography and a high throughput nanoparticle immunoassay (My5-FU) have been used in conjunction with treatment algorithms to guide dosing. The objective of this study was to assess accuracy, clinical effectiveness and safety of plasma 5-fluorouracil guided dose regimen(s) versus standard regimens based on body surface area in colorectal cancer. Methods We undertook a systematic review. MEDLINE; MEDLINE In-Process & Other Non-Indexed Citations; EMBASE; Cochrane Library; Science Citation Index and Conference Proceedings (Web of Science); and NIHR Health Technology Assessment Programme were searched from inception to January 2014. We reviewed evidence on accuracy of My5-FU for estimating plasma 5-fluorouracil and on the clinical effectiveness of pharmacokinetic dosing compared to body surface area dosing. Estimates of individual patient data for overall survival and progression-free survival were reconstructed from published studies. Survival and adverse events data were synthesised and examined for consistency across studies. Results My5-FU assays were found to be consistent with reference liquid chromatography tandem mass spectrometry. Comparative studies pointed to gains in overall survival and in progression-free survival with pharmacokinetic dosing, and were consistent across multiple studies. Conclusions Although our analyses are encouraging, uncertainties remain because evidence is mainly from outmoded 5-fluorouracil regimens; a randomised controlled trial is urgently needed to investigate new dose adjustment methods in modern treatment regimens.